Reconstruction and Development of Indonesian Language PAT Question Items Aspects of Class VII Literary Expression MTs N 1 Banjarnegara Academic Year 2021/2022 - Legi Aspriyanti; Risky Arbangi Nopi; Wangiran; Deby Luriawati Naryatmojo (Journal of Educational Analytics, 2022)
Assessment in the 2013 curriculum is seen as having more complexity than the assessment system in the previous curriculum. So that in this study will discuss "Reconstruction and Development of Instruments for Assessment of Indonesian Language Learning Outcomes Aspects of Literary Expression for Class VII Students of MTs 1 Banjarnegara for the 2021/2022 Academic Year" as an effort to reduce errors in making assessment questions about aspects of literary expression and present a form of improvement for errors that have been conducted. The approach in this research is a qualitative approach. The type of research used is content analysis research. Data analysis refers to the rules for writing questions contained in the 2013 Curriculum Assessment Guide issued by the Ministry of Education and Culture with due regard to material, construction, and language/cultural aspects. The results showed that there were still 2 Indonesian Year End Assessment (PAT) questions for class VII MTs 1 Banjarnegara for the 2021/2022 academic year in terms of literary expression which did not meet good quality standards.